Cutaneous and Visceral Leishmaniasis: Parasites, Vectors and Reservoir Hosts in Endemic Foci of North Khorasan, Northeastern Iran- a Narrative Review - Sadaf Sabzevari; Mehdi Mohebali; Ahmad Hashemi (Pasteur Institute of Iran, 2020)
Leishmaniases are tropical diseases caused by various types of intracellular protozoan species of the genus Leishmania. The infection is transmitted to vertebrate hosts by the infective bite of female sandflies. Depending on the location of the parasite in mammalian tissues and Leishmania species, leishmaniasis presents at least three primary clinical forms: visceral (VL), cutaneous (CL), and mucocutaneous (MCL). Iran is one of the significant endemic areas for CL in Asia. Here, we comprehensively reviewed the literature published from 2009 to 2019 and focused on the distribution, clinical aspects, causatives agents, reservoirs, and vectors of CL and VL in different parts of North Khorasan Province, northeast of Iran. North Khorasan Province in northeastern Iran is one of the principal foci of CL, but VL is just known as an endemic parasitic disease in some areas of this province. Based on a comprehensive literature search on studies published from 2009 to 2019, distribution, causatives agents, reservoirs, and vectors of CL and VL in different parts of North Khorasan Province were determined. Zoonotic cutaneous leishmaniasis )ZCL( due to Leishmania major is the main form of CL in this province. The principal animal reservoir hosts of the infection are rodents and Ph. sergenti is the most predominant species. VL, caused by Leishmania infantum, occurs in some parts of the province, and wild canines were confirmed as reservoirs.